Ecological Responses of Three Bird Species to the Urban Landscape: Habitat Suitability and Connectivity in DKI Jakarta - Ady Kristanto; Tatang Mitra Setia; Nurul Laksmi Winarni (Universitas Nasional Jakarta, 2026)
Urbanization alters habitat structure and the ecological connectivity of urban wildlife. This study evaluated habitat suitability and connectivity for three bird species with contrasting ecological strategies—the Red-breasted Parakeet (Psittacula alexandri), Brown-throated Sunbird (Anthreptes malacensis), and Olive-backed Tailorbird (Orthotomus sepium)—in DKI Jakarta. Habitat suitability was modeled using MaxEnt with six environmental variables, while connectivity was analyzed using a circuit-theory approach in Circuitscape. The MaxEnt models yielded AUC values of 0.755–0.791, indicating fair predictive performance. The principal determinants differed among species: population density dominated the Red-breasted Parakeet model (52.7%), NDVI dominated the Brown-throated Sunbird model (40.6%), and land use dominated the Olive-backed Tailorbird model (41.0%). NDVI was consistently the most important variable according to permutation importance. Highly suitable habitat covered 9.6–19.5% of the study area. Connectivity analysis revealed contrasting patterns: the Red-breasted Parakeet exhibited centralized connectivity through narrow pinch points, whereas the Brown-throated Sunbird and Olive-backed Tailorbird displayed more diffuse corridor networks. Monas and Gelora Bung Karno consistently functioned as both habitat and connectivity hubs for all three species, making them priority areas for urban bird conservation in Jakarta.